Effects of pregnanolone in rats discriminating cocaine - Quinton, M.S. (2006)
The discriminative stimulus effects of cocaine are typically attributed to its ability to increase dopaminergic transmission, although drugs that have different mechanisms of action can substitute for cocaine and modulation of the GABA(A) receptor system has been reported to alter its discriminative effects. Therefore, a discrimination procedure was used to extend the characterization of cocaine’s discriminative effects and to examine the interaction between cocaine and pregnanolone, a drug that can modulate the GABA(A) receptor complex. Rats (n=15) were trained to discriminate saline from 5.6 or 10 mg/kg of cocaine under a fixed-ratio (FR) 20 schedule of food presentation. The dopamine releaser d-amphetamine and two monoamine uptake inhibitors bupropion and desipramine substituted for cocaine. In contrast, the positive GABA(A) modulators pregnanolone and lorazepam and the opioid agonist morphine did not substitute for cocaine. When administered prior to cocaine, the D(2) receptor antagonist haloperidol and pregnanolone, but not lorazepam, produced a small rightward shift of the cocaine dose-effect curve. The results of the present studies suggest that the discriminative stimulus effects of cocaine are not solely mediated by increases in dopaminergic transmission and that positive modulation of GABA(A) receptors by pregnanolone can alter these effects, albeit at doses that also decrease overall response rate.